The implication of FDI in the construction industry in Cambodia under BRI - Bora Ly (Taylor & Francis Group, 2021)
There is clear evidence that building infrastructure contributes to a country’s rising economy and improved well-being. Belt and Road Initiative (BRI) expansion operations are mainly designed to make the infrastructure necessary and increase physical connectivity. The purposes of this article are to discuss the implication of FDI in Cambodia under the BRI initiatives on Diamond Island and Golden Silver Gulf Resort as the cases. This work uses a qualitative method and two theoretical frameworks of Ownership-Location-Internalization (OLI) and Investment Development Path (IDP) to investigate the cases. The inward FDI returns in Cambodia have triumphed, but not they all have been met so far. However, it can be a way of hindering potential benefits to spillover effects and obstacles for Cambodian workers.